2021
DOI: 10.1038/s41409-021-01368-w
|View full text |Cite
|
Sign up to set email alerts
|

A bioinspired and chemically defined alternative to dimethyl sulfoxide for the cryopreservation of human hematopoietic stem cells

Abstract: The cryopreservation of hematopoietic cells using dimethyl sulfoxide (DMSO) and serum is a common procedure used in transplantation. However, DMSO has clinical and biological side effects due to its toxicity, and serum introduces variation and safety risks. Inspired by natural antifreeze proteins, a novel class of ice-interactive cryoprotectants was developed. The corresponding DMSO-, protein-, and serum-free cryopreservation media candidates were screened through a series of biological assays using human cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Specifically, it was found that an apparent >90% viable population 1 h post-thaw decreased to less than half that (between 20–40%) by 24 h post-thaw following hHPC cryopreservation using traditional culture media with 5 or 10% DMSO ( Figure 1 ). This finding was consistent with previous reports that describe HPC and/or HSC post-thaw viability to range between 40 and 60% of pre-freeze controls with varying cryopreservation media formulations and cryoprotective agents, including 10% DMSO [ 64 , 88 , 95 , 96 , 97 , 98 , 99 , 100 ]. When samples were cryopreserved using Unisol™, overall hHPC viability at 24 h post-thaw increased to 60–65% depending on the DMSO concentration ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Specifically, it was found that an apparent >90% viable population 1 h post-thaw decreased to less than half that (between 20–40%) by 24 h post-thaw following hHPC cryopreservation using traditional culture media with 5 or 10% DMSO ( Figure 1 ). This finding was consistent with previous reports that describe HPC and/or HSC post-thaw viability to range between 40 and 60% of pre-freeze controls with varying cryopreservation media formulations and cryoprotective agents, including 10% DMSO [ 64 , 88 , 95 , 96 , 97 , 98 , 99 , 100 ]. When samples were cryopreserved using Unisol™, overall hHPC viability at 24 h post-thaw increased to 60–65% depending on the DMSO concentration ( Figure 2 ).…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, recognition of the critical role cryopreservation plays in the success of the field of regenerative medicine remains a hurdle. In an effort to address these challenges and improve the outcome, today’s researchers are focused on developing new CPAs [ 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], targeted apoptotic control [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ] during cryopreservation and new devices [ 69 , 70 , 71 ]. On the discovery science side, groups continue to investigate the pathways activated during cryopreservation, as well as during the recovery phase [ 72 , 73 , 74 , 75 , 76 , 77 ].…”
Section: Introductionmentioning
confidence: 99%
“…These properties of natural AFPs have recently inspired the development of new ice-interactive cryoprotectants that have been used as an alternative to DMSO in the cryopreservation of human hematopoietic stem cells [ 52 ].…”
Section: Natural Cryoprotective and Cytoprotective Agentsmentioning
confidence: 99%
“…However, ice crystal formation occurs throughout the cells during the freezing process if the cells are not sufficiently dehydrated. It is necessary to investigate vitrification and slow freezing with chemically defined freezing solutions (such as ethylene glycol, polyethylene glycol) without DMSO [ 27 , 31 ]. Damage-sensitive cells could be recovered by devising a suitable freezing strategy and optimizing the composition of the freezing solution.…”
Section: Discussionmentioning
confidence: 99%
“…A chemically defined solution without DMSO using vitrification was effective for the cryopreservation of human embryonic stem cells (ESCs) [ 27 ]. The use of a chemically defined solution using slow freezing for the cryopreservation of pluripotent stem cells and tissue stem cells have been widely reported [ 30 , 31 ]. Cell therapy with cellular and tissue-based products, such as Kymriah (Tisagenlecleucel) and TEMCELL HS Inj.…”
Section: Introductionmentioning
confidence: 99%